In Vitro Regenarationof Artemisia Annua (Wormwood) Using Seed Explants - S. M, Tahir; I.S, Usman; M. D, Katung; M. F, Ishiyaku (The International Journal of Biotechnology, 2013)
The most effective concentration of some plant growth hormones on the in vitro regeneration of Artemisia annua using seed explants was investigated in the Biotechnology Laboratory of Plant Science Department of Ahmadu Bello University, Zaria. Fresh and healthy seeds of a Chinyong variety were sourced, sterilized and inoculated on a full and half strengths Murashige & Skoog basal media supplemented with varying concentrations of plant growth hormones using the procedure of Hamish, 1998. Combined treatment of GA3 (1.0 µm/l) and NAA (0.5 µm/l) in a half strength MS media recorded the fewer days to germination. Highest germination percentage was observed at combination of GA3 (2.0 µm/l) and BAP (0.5 µm/l) in a full strength MS media. Equal concentration of combined GA3 and BAP (ie 0.5 µm/l) in a full strength MS media had the best vigor, followed by varying concentration of GA3 (2.5 µm/l) and NAA (0.5 µm/l) in a half strength MS media. Highest seedling height was observed at equal concentration of combined GA3 and BAP (ie 0.5 µm/l) in a full strength MS media. This was followed by varying concentration of GA3 (0.5 µm/l) and NAA (1.0 µm/l) in a full strength MS media. Result of Analysis of Variance indicated significant difference among some of the treatments compared with the control (P≤0.05). Treating Artemisia seeds using these plant growth hormones had reduced the effect of the phenolic secretions reported on the seeds thereby enhancing its germination. Therefore, this is a promising approach to faster in vitro regeneration of Artemisia plant.